Studying the Quality of Colloquial Infinitives in Moin Persian Dictionary - شکوهی پریسا (LANGUAGE ART, 2017)
Mohammad Moin has been considered as one of the most committed literary men of the present time who recorded a considerable amount of Persian words, expressions, and declarations in his own 6 volumes Persian dictionary according to scientific research methods and in a different way in comparison to the previous dictionaries. This article argues the quality of colloquial infinitives which have been recorded in Moin Persian Dictionary. The most important obstacles in all researches related to literature and colloquial language is the recognition criterion of "being colloquial". In this article, the recognition criterion is that of Moin’s criterion who was a great master in this field. In the other words, any infinitives in front of which he put the abbreviation "Ɂam", have been extracted and at the next stage, according to the syntactic resources, have been divided into 8 categories. Finally, the examples of each category have been presented through tables.